2016
DOI: 10.1186/s40560-016-0173-0
|View full text |Cite
|
Sign up to set email alerts
|

An overview of point-of-care ultrasound for soft tissue and musculoskeletal applications in the emergency department

Abstract: BackgroundThe skin, soft tissue, and most parts of the musculoskeletal system are relatively superficial anatomical structures and ideal targets for ultrasound examination in the emergency departments. Soft tissue and musculoskeletal ultrasound applications are relatively underused compared to traditional emergency applications, such as trauma, abdominal aortic aneurysm, and chest and cardiovascular systems.Main textIt is important to have knowledge about sonoanatomy and landmarks within the skin, soft tissue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 50 publications
(41 reference statements)
2
29
0
2
Order By: Relevance
“…37,55 Echo guidance can be used to identify the vessel or to advance the needle under real-time ultrasound guidance. 56 The use of real-time ultrasound and experience with the procedure reduce the complication rate. 46,52,54 Real-time ultrasound guidance was not yet available at the time of all studies we included, and this may have caused bias between studies.…”
Section: Discussionmentioning
confidence: 99%
“…37,55 Echo guidance can be used to identify the vessel or to advance the needle under real-time ultrasound guidance. 56 The use of real-time ultrasound and experience with the procedure reduce the complication rate. 46,52,54 Real-time ultrasound guidance was not yet available at the time of all studies we included, and this may have caused bias between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, point-of-care ultrasound (POCUS) has been increasingly used at patients’ bedside for diagnostic and therapeutic purposes [10, 11] . POCUS also enables emergency or primary care physicians to quickly recognize musculoskeletal and soft tissue disorders and to provide better and safer cares [12]. Kelm et al revealed that a longitudinal curriculum for POCUS enhanced knowledge retention and the ability to recognize pathological findings for internal medicine residents [13].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis can often be made by history and clinical examination alone, however, up to 20% of these ruptures can be missed in the initial hyperacute phase [ 10 ]. A delay in diagnosis will lead to a delay in treatment which in turn can lead to a difficult repair; this leads to a poorer function in performance and strength for the patient [ 10 , 11 ].…”
Section: Reviewmentioning
confidence: 99%